Os objetivos das visitas escolares a um observatório astronômico na visão dos professores - Fernando Roberto da Costa Linhares (2011)
Among the many issues that museums, science centers and other scientific popularization places may broach, the Astronomy is the branch than raises more curiosity and fascination between people of all ages. Thus, spaces that provide the teaching and the popularization of this science for several types of public, like the astronomical observatories, become importants as being an alternative that contribute to solve the deficiences detected at formal spaces. Nevertheless, at most of the time, such places have some features which get to damage their use by the school community, such as: the small number of designed places to this role, once mentioned the country territorys large extension; the divulgation absence, which makes that much of the teachers do not yet know about this places or even their localization; and the restricted working time, often nocturnal, which fix the access as unavailable to several schools. Moreover, it happens than the Astronomy is not to be a school subject, and even less is claimed on tests or vestibular tests. Despite this, what is noted is a large search by the teachers, that otherwise face all the put difficulties, including all the responsibility they bring to themselves when they do manage a nightly school travel to another city with children and teenagers. Thence, this research has sought investigate the objectives of the teachers that regularly undertake school visits to the Observatio Astronico Frei Rosio, a very important place for teaching, divulgation and popularization of Astronomy, situated at the metropolitan region of the Belo Horizonte city. Taking as database all of the subscription record cards related to the school visits that occurred on interval from 1997 to 2009, it has been possible to make a quantitative study about the visitors schools and the school visits on the reference period, as well as, from it, identify some teachers which have made regular visits to that place. Next, by interviewing ten of these teachers, we have realized which were the objectives that took them to visit that place with your students. Weve verified that all of them clearly have had a direct objective, and also many other indirect objectives, which showed the end purpose of school excursions and the way they realized and have used that space. One of the gotten results was that, for this ten teachers set, the astronomical observatory has the role of a Astronomy teaching space or of one of Astronomy popularization, whereas for eight teachers its a space where occurs teaching (formal education) of Astronomy, or of Sciences in general, and for only two of them its a space where occurs Astronomy popularization (non-formal education). Through this study it has even been possible to discuss other relevant questions to this research field, which have not been much exploited by the area researchers, in the sense to indicate improvements to the Astronomy teaching at the astronomical observatories and at other non-formal places, in order to popularize their use by the teachers and, whence, increase the educational potential of such spaces.